National utilization of rib fracture fixation in the geriatric population in the United States - Jennifer M. Brewer; Leah Aakjar; Kelsey Sullivan; Vijay Jayaraman; Manuel Moutinho; Elan Jeremitsky; Andrew R. Doben (Journal of Trauma and Injury)
Purpose The use of surgical stabilization of rib fractures (SSRF) has steadily increased over the past decade. Recent literature suggests that a larger population may benefit from SSRF, and that the geriatric population—as the highest-risk population—may receive the greatest improvement from these interventions. We sought to determine the overall utilization of SSRF in the United States. Methods The National Trauma Database was analyzed between 2016 and 2017. The inclusion criteria were all patients ≥65 years old with rib fractures. We further stratified these patients according to age (65–79 vs. ≥80 years old), the presence of coding for flail chest, three or more rib fractures, and intervention (surgical vs. nonoperative management). The main outcomes were surgical interventions, mortality, pneumonia, length of stay, intensive care unit length of stay, ventilator use, and tracheostomy. Results Overall, 93,638 patients were identified. SSRF was performed in 992 patients. Patients who underwent SSRF had improved mortality in the 65 to 79 age group, regardless of the number of ribs fractured. We identified 92,637 patients in the age group of 65 to 79 years old who did not undergo SSRF. This represents an additional 20,000 patients annually who may benefit from SSRF. Conclusions By conservative standards and the well-established Eastern Association for the Surgery of Trauma clinical practice guidelines, SSRF is underutilized. Our data suggest that SSRF may be very beneficial for the geriatric population, specifically those aged 65 to 79 years with any rib fractures. We hypothesize that roughly 20,000 additional cases will meet the inclusion criteria for SSRF each year. It is therefore imperative that we train acute care surgeons in this skill set.